2019
DOI: 10.1111/clr.13541
|View full text |Cite
|
Sign up to set email alerts
|

The impact of graft remodeling on peri‐implant bone support at implants placed concomitantly with transcrestal sinus floor elevation: A multicenter, retrospective case series

Abstract: Objectives:To evaluate the impact on peri-implant bone support (as assessed on periapical radiographs) of the remodeling dynamics of varying graft biomaterials used for transcrestal sinus floor elevation (tSFE). Methods:The study is a multicenter, retrospective series of cases undergone tSFE (performed according to the Smart Lift technique) and concomitant implant placement. At operator's discretion, tSFE was performed with bone core (BC) alone or supplemented by deproteinized bovine or porcine bone mineral (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 62 publications
(129 reference statements)
6
27
0
Order By: Relevance
“…Consistently, marginal, peri-implant bone loss has been reported between re-entry for uncovering and final prosthesis delivery by other authors (Cardaropoli, Lekholm, Wennstrom, 2006, Nader et al, 2016. It should also be considered that, in some patients of the (Franceschetti et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistently, marginal, peri-implant bone loss has been reported between re-entry for uncovering and final prosthesis delivery by other authors (Cardaropoli, Lekholm, Wennstrom, 2006, Nader et al, 2016. It should also be considered that, in some patients of the (Franceschetti et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…In the SPAL dehiscence group, therefore, the extent of graft remodeling at interproximal sites may have negatively impacted on RBL values. Recent data have shown that even slowly resorbable graft biomaterials, such as DBBM, are associated with a substantial reduction of the grafted area at 12‐month radiographic evaluation following endosinusal augmentation procedures (Franceschetti et al., 2019). However, the magnitude of RBL observed in the present study is limited compared to that reported for implants placed with concomitant GBR or in native bone (Urban et al., 2019) and implants presenting an untreated buccal dehiscence (Jung et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study of 89 patients receiving implants concomitantly with the Smart Lift technique (Trombelli, Minenna, Franceschetti, Minenna, & Farina, ; Trombelli, Minenna, Franceschetti, Minenna, Itro, et al, ) reported that the remodelling process of graft biomaterials followed a cranial–caudal direction. In the DBBM treatment group, a significant reduction of the proportion of the implant surface in direct contact with the radiopaque area was observed from 6 to 36 months (Franceschetti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The edentulous posterior maxillary region poses an especially relevant clinical challenge since sinus pneumatization following tooth loss speeds up the progression of alveolar bone loss (Esposito, Felice, & Worthington, 2014). In these cases, rehabilitation with dental implants usually demands grafting procedures (i.e., sinus bone graft, or sinus lifting) prior to or along with implant placement (Franceschetti et al., 2020; Stacchi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%